Identifying the Factors That Drive Health Service Utilization Among Healthy and Non‐Healthy Agers in a Sample of Older Ethiopians: A Cross‐Sectional Study - Amare Belachew; Nicolas Cherbuin; Nasser Bagheri; Richard Burns (Health Science Reports)
ABSTRACT Background and Aims Population aging is associated with the rising incidence of chronic illness. This presents a significant challenge to healthcare systems, particularly in developing countries, as untreated chronic conditions can lead to years of disability and loss of independence straining health budgets and resources. Promoting healthy aging can be one avenue for mitigating these challenges. This study aims to identify factors influencing health service use among healthy and non‐healthy agers, utilizing the Andersen‐Newman model that describes predisposing (including demographic characteristics, social structure, and health beliefs), enabling (related to the logistical aspects of obtaining care, such as personal and community resources), and need factors (referring to the individual's perceived and evaluated health status). Methods Older adults (n = 545) in Bahir Dar, Ethiopia were surveyed about their health and health‐seeking behaviors. Associations between risk factors and health service utilization were examined using Poisson regression with robust standard errors. Results A total of 79.3% of older adults utilized health services, with consistent usage between healthy and non‐healthy agers. Factors associated with increased health service utilization included severe (RR = 2.20; 95% CI: 1.56–3.09), and moderate (RR = 2.03; 95% CI: 1.44–2.85) disease severity, reporting comorbid conditions (RR = 1.14; 95% CI: 1.06–1.23), having health insurance (RR = 1.14; 95% CI: 1.05–1.23), not reporting loneliness (RR = 1.13; 95% CI: 1.02–1.26), and being financially independent (RR = 1.11; 95% CI: 1.00–1.22). Conversely, residing in rented housing (RR = 0.78; 95% CI: 0.62–0.98) and living greater than 30 min from a healthcare facility (RR = 0.62; 95% CI: 0.54–0.71) decreased health service utilization. Conclusion Health service utilization was low compared to developed countries. This could be due to newer and improved health services in developed countries. Improving financial independence, health insurance coverage, access to healthcare facilities, and encouraging peer or family support can enhance healthcare access in Ethiopians.